Principal Strategy In Improving The Quality Of Islamic Education Institution In Integrated Islamic Elementary School Cahaya Hati Kota Bukittinggi - Elvi Rahmi (Pusdikra Publishing, 2021)
The principal's strategy is one of the most important elements in improving the quality of education, therefore the principal is responsible for organizing educational activities in schools. Therefore, the principal must be able to be a good manager in order to improve the quality of education, both in terms of quantity and quality. Improving the quality of education is one of the key indicators for looking at productivity related to the management carried out by the principal. This study aims to see the principal's strategy in improving the quality of schools through fostering teacher competence and internalizing learning programs in improving the quality of education in schools. To achieve this goal, this study uses a qualitative descriptive approach and data collection techniques in the form of observation, interviews and documentation. The results showed that (1) the principal's strategy through fostering teacher competence was running well, this can be seen from the skills possessed by the teacher in the learning process, besides that the teacher also has broad insights about changes and improvements to the education system both regarding curriculum issues. and school management. (2) The principal's strategy is through internalizing the learning program, namely providing direction and guidance to teachers through internalization into the syllabus and lesson plans so that the teacher in the learning process gives the best to students.